DISTANT EDUCATION IN DENTISTRY: ORGANIZATION AND ECONOMIC EFFECTIVENESS - A.A. KALININSKAYA; YA.V. MOROZOVA; V.M. LEVANOV (Avicenna Tajik State Medical University, 2017)
Objective: Study of the possibilities of applying distant education technologies within the framework of the model of short-term (18-36-hour) advanced training courses in additional professional programs. Methods: As an example of the proposed model, the distant course «Burning questions of dentistry» was organized by medical universities - the Moscow State Medical-Stomatological University named after A.I. Evdokimov, Nizhny Novgorod State Medical Academy, and Belgorod State National Research University. Questioning on the attitude of doctors to the application of distant education technologies was conducted among 138 dentists. Economic efficiency is calculated by the technique of E.N. Kulagina and I.I. Vvedenskaya, 1998. Results: The subjects of video lectures were agreed between the parties and included a wide range of questions on the diagnosis, treatment, and prevention of dental diseases. The text of lectures was accompanied by slides, which were demonstrated synchronously with the text of the lecture. At the end of the video lecture, the lecturer was asked questions from students for 10-15 minutes. In order to identify the possibility of reducing the economic costs of continuing professional education of physicians while maintaining a high quality of education, a comparative analysis of full-time, away and distant courses was conducted. The difference in the total cost of the courses depends on the travel expenses of studies in the full-time cycle, the teachers - in the tour cycle and the costs of equipment depreciation and payment for communication services - in the remote cycle. The costs of distant education directly depend on the number of students. Readiness for distant forms of education was expressed mainly by doctors who have experience in using informative communication technologies in their work and everyday life. The conducted sociological surveys revealed a preference for the use of tele-education technologies over the needs in teleconsultations. Conclusion: The main advantage of the short-term courses is the ability to quickly learn the latest technologies and methods of diagnosis, treatment, prevention, and rehabilitation. The use of distant education technologies significantly reduces the cost of courses and allows organizing training on flexible schedule. Distant courses are highly informative and not inferior to traditional forms of education. The program of the course can use any telemedicine technologies and forms of organization of studies (video lectures, webinars, scientific and practical conferences, etc.). The questionnaire showed a predominantly positive attitude of doctors towards the use of distant education technologies.